What is noise for the motion system? - Scase, M; Braddick, O; Raymond, J (1996)
Motion coherence thresholds in random-dot patterns have been widely adopted as a measure of performance in visual motion processing. However, there has been diversity in the type of "noise" in which a coherent motion signal has to be detected. Here we compare coherence thresholds for three ways of creating motion noise: dots replotted in random positions in each new frame; dots with a set displacement but following a random walk from frame to frame; or dots moving in random directions which remain constant for a given dot over a sequence of displacements. In each case, the signal dots may either remain the same throughout the display sequence, or the signal dots may be re-selected afresh on each frame ("different"). With our display (3 deg square, 120 msec exposure, velocity = 5 or 10 deg sec-1), all these different noise conditions yielded similar thresholds around 5-8%. There were some small but systematic differences between conditions. Thresholds in random-direction displays were consistently higher than those in random-walk or random-position displays, especially at the lower velocity. However, this effect is much smaller than would be expected from the increased standard error of the noise mean in random direction, perhaps because the motion system integrates information most effectively over a local region of space and/or time. Subjects" performance could not be explained by a strategy of identifying individual signal dots with extended trajectories. The similarity between random-walk and random-position thresholds implies that subjects do not exploit the marked differences in speed distribution between signal and noise dots in the latter case. The practical message for the design and interpretation of experiments using coherence thresholds is that the results are not much affected by the choice of noise, at least within the range of stimuli tested here.